1.105. Wykaż, że: a) 1-log 1 ^ 1 3 (log 2 3+log 3 2+1)log 2 2 3 =log 2 3 ((log2 7 + log7 2 + 2) * log 2)/(log2 2 + 1) = log 14 b) 8+log 2 ^ 3 5 log 5 16+log 1 5-2 +1= 1 log^ 2 2 (log 5 ^ 2 2-1)* log 2 5 log 2 5+log 5 2+2 =log 2 5 b) log2 5 = b , d) oblicz log2 400 log3 2 = a , oblicz b) log6 2 = a * log6 5 = b , oblicz log36 0, 8 d) og 2 3=a log 3 5=b , oblicz log2,200 b) log3 20 = a * log3 15 = b , oblicz log2 360 d) log2 30 = a * log2 36 = b , oblicz log 9 log6 16 pi/3 c)

1.105. Wykaż, że: a) 1-log 1 ^ 1 3 (log 2 3+log 3 2+1)log 2 2 3 =log 2 3 ((log2 7 + log7 2 + 2) * log 2)/(log2 2 + 1) = log 14 b) 8+log 2 ^ 3 5 log 5 16+log 1 5-2 +1= 1 log^ 2 2 (log 5 ^ 2 2-1)* log 2 5 log 2 5+log 5 2+2 =log 2 5 b) log2 5 = b , d) oblicz log2 400 log3 2 = a , oblicz b) log6 2 = a * log6 5 = b , oblicz log36 0, 8 d) og 2 3=a log 3 5=b , oblicz log2,200 b) log3 20 = a * log3 15 = b , oblicz log2 360 d) log2 30 = a * log2 36 = b , oblicz log 9 log6 16 pi/3 c)

Kliknij aby dołączyć do Akademii Matematyki

Dodaj komentarz